Determination of the conversion coefficients from the dose-length product to the effective dose for CT-examinations of the whole body including lower extremitie - P. S. Druzhinina; L. A. Chipiga; A. V. Vodovatov; I. V. Soldatov; Z. A. Lantukh; K. V. Tolkachev (Радиационная гигиена)
Today in the Russian Federation, the existing method for assessing patients` effective doses during computed tomography in the form of conversion coefficients from the dose-length product provides for the area from the head to the upper third of the femur but does not consider the possibility of scanning the whole body including the lower extremities. In this case, for some nosologies, the lower extremities may be involved. The aim of the study was to develop conversion coefficients from the dose-length product to the effective dose for whole-body computed tomography scanning including the patient's lower extremities. The coefficients for whole-body computed tomography scans (including the lower extremities) were determined for a sample of computed tomography scanners that are part of positron emission tomography combined with computed tomography devices of different models for adults and children of different age groups. In NCICT 3.0 software absorbed organ doses were calculated taking into account the specific model of devices and scan length. Effective doses were determined in accordance with the methodology presented in Publication 60 of the International Commission on Radiological Protection and Radiation Safety Standards 99/2009. Separately, conversion coefficients were developed from the dose-length product to the absorbed dose in uterus to enable predictive assessment of doses in the fetus in pregnant women. The study presents the average values of the received effective doses, absorbed doses in uterus and conversion coefficients for all considered models of devices. Conversion coefficients for protocols with automatic tube current modulation were lower compared to those for protocols without automatic tube current modulation, especially for pediatric patients: for children with an average age of 0 years – 9 times, for children an average age of 1 year – 6 times, for children an average age of 5 years – 5 times, for children an average age of 10 years – 3 times, for children an average age of 15 years – 2 times; for adults the difference was 20%. Comparison of the conversion coefficients from the dose-length product to the effective dose for computed tomographic scanning of the whole body area limited to the upper third of the femur, presented in guidelines 2.6.1.3584-19, with the values obtained in this study for the whole body area with the lower extremities without automatic tube current modulation showed that for all age groups, with the exception of newborns, the conversion coefficients for the scanning area with the lower extremities are lower than those presented in the guidelines. Using the conversion coefficients from the Guideline 2.6.1.3584-19 for whole-body computed tomography scanning with the lower extremities will lead to a significant overestimation of patient doses. The calculated conversion coefficients from the dose-length product to the absorbed dose in uterus and from the dose-length product to the effective dose for computed tomography examination of the whole body with the lower extremities for different age groups of patients are suitable for assessing the effective doses of patients and for prognostic estimates of absorbed dose in the fetus in pregnant women.